PENGEMBANGAN E-FLIPBOOK ENZIM BERDASARKAN UJI PENGHAMBATAN EKSTRAK SIMPUR (Dillenia suffruticosa) TERHADAP ENZIM ?-GLUKOSIDASE - Muhammad Nijam (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2020)
The aims of this research were to develop e-flipbook on enzyme material based on the inhibitory activity test of extract Dillenia suffruticosa, to determine it’s feasibility, to know the students’ response about e-flipbook towards it’s usage on classroom. To achieve the aims, a set of procedures from Borg and Gall model was applied. In order to determine feasibility, nine experts consisting of three material experts, three linguistic experts and three media experts were asked to fill validity questionnaires. Furthermore, in order to know students’s response, thirty students of Chemistry Education FKIP Untan were asked to fill response questionnaires. According to data analysis, the e-flipbook had assessment from expert that included of material aspect (93,75%), linguistic aspect (93,75%), and media aspect (91,67%). Based on the questionnaire responses of undergraduate students to e-flipbook, the result was 78,87%. In conclusion, e-flipbook was successfully developed with excellent feasibility, and students’s response towards its usage was excellent as well.Keyword : e-flipbook, enzyme, simpur plant, ?-glucosidase enzyme